Lecturer Teaching Methods And Competences And Students Learning Achievement - Mindani Mindani (At-Ta'lim : Media Informasi Pendidikan Islam, 2019)
Abstract: Lecturer Teaching Methods And Competences And Students Learning Achievement The use of lecturers 'teaching methods and competencies varies greatly at IAIN Bukittinggi and it is important to know the relationship between lecturers' teaching methods and competencies with student learning achievements at Bukittinggi IAIN. The quantitative descriptive method used can clearly identify the relationship between the method and teaching competence of 40 lecturers with student learning achievement. The method of teaching lecturers at IAIN Bukittinggi mostly uses lecture and question and answer methods, discussion, assignment and reading and problem solving. Teaching competence of lecturers at IAIN Bukittinggi in the teaching and learning process is quite high in terms of mastery of the material, syllabus development and KRS preparation, implementation of learning and teaching interactions, and student achievement. The method and teaching competence of lecturers do not correlate with student achievement at IAIN Bukittinggi, only reaching 2.8% of student achievement, the rest is more influenced by other factors.Abstrak : Metode dan Kompetensi Dosen Serta Prestasi Belajar Mahasiswa  Penggunaan metode pengajaran dan kompetensi dosen yang bervariasi di IAIN Bukittinggi sangat penting untuk mengetahui hubungan antara metode pengajaran dan kompetensi dosen dengan prestasi belajar mahasiswa di IAIN Bukittinggi. Metode deskriptif kuantitatif yang digunakan dapat dengan jelas mengidentifikasi hubungan antara metode dan kompetensi mengajar 40 dosen dengan prestasi belajar mahasiswa. Metode pengajaran dosen di IAIN Bukittinggi sebagian besar menggunakan metode ceramah dan tanya jawab, diskusi, pemberian tugas dan pemecahan masalah. Kompetensi mengajar dosen di IAIN Bukittinggi dalam proses belajar mengajar cukup tinggi dalam hal penguasaan materi, pengembangan silabus dan mempersiapkan KRS, pelaksanaan pembelajaran dan interaksi pengajaran, serta prestasi belajar mahasiswa. Metode dan kompetensi mengajar dosen tidak berkorelasi dengan prestasi belajar mahasiswa di IAIN Bukittinggi, hanya mencapai 2,8% dari prestasi belajar mahasiswa, sisanya lebih dipengaruhi oleh faktor lain.